San Martín and Bolívar: The debates between the English and Irish legionaries on the merits of the liberators - Wu Brading, Celia (2021)
The article traces the origins of the debate from a select group of English and Irish legionaries, especially Sir Belford Hinton Wilson and General William Miller, who served under San Martín and Bolívar. It also reveals the divergent opinions held about both characters by their English and Irish supporters, which reflect the opinions and prejudices of Spanish-American generals, ideologues and politicians of the independence era, which is maintained to this day when comparing the contrasts between the figure and work of the two great liberators.